An Examination of Customer Misbehaviour in Malaysia - Chong, Wai Yip (2007)
The aim of the research is to identify the common traits of customer misbehaviour and the motives behind such deviant acts in Malaysia. It is also aims to find out which service industries are prone to customer misbehaviour. Services have become part of everyone’s life, be it going to the cinema, taking a train, or dining in the restaurant. Customers that are physically present in the service area for consumption of goods and services are given the opportunity to misbehave, be it in the form of vandalism, pilfering or other unpleasant deeds. ‘Aberrant Consumer Behaviour’, a conceptual theory by Ronald A. Fullerton and Girish Punj and Christopher Lovelock’s the ‘Jaycustomer’ theory was used as the basis of this research. After reviewing the existing literature, a quantitative research was conducted to address the issues highlighted in the questionnaire posted on the Internet. The findings from a sample of 78 were then analysed and discussed. The result of the study was deemed useful to provide insights on customer misbehaviour in the context of Malaysia. It identified customers as being afraid to admit to their deviant acts; however, it was able to provide insights on the motives behind those acts. Most of the customers think that their deviant acts are impromptu or spontaneous and motivated by the unhelpful, inattentive, impolite and not informative service personnel. Service industries, like restaurants and service centres were found to be more prone to customer misbehaviour than others and solutions were suggested to these organisations/firms to minimise or avoid such deviant acts.